A mediação da leitura no âmbito das Bibliotecas Digitais - Nascimento, Raquel da Silva (2019)
This research addresses reading and reading practices carried out through the collections of digital libraries, observing the relationships among reading, users and knowledge from online access to works of historical and cultural value mediated by these digital environments. We propose to use as a resource for the empirical research of mediation of digital collections, the dossier “França no Brasil”, conceived through a partnership between the national libraries of Brazil and France, in which the documents portray the history, relationships and influences between Brazilian and French cultures, making important collections available to users that picture the relationship between these two countries. Digital collections allow a comprehensive reach to works which are considered rare, fragile or are at risk and may not have the alternative of physical access, remotely and instantly. In the dynamics between the reader and the reading, we can see mediation and the complexities that surround them. In this way, we identified it as a dynamic and transforming process with the interpretations and reflections of the subjects. Linked to libraries, the relationship with reading is recognized in a path that involves social, cultural and educational aspects, as well as the impacts and transformations caused by digital technologies. The aim was to investigate the relevance of reading mediation for the appropriation and dissemination of information and knowledge, in order to better understand how reading occurs in the social, cultural and technological context of digital libraries by readers. We seek to clarify these concerns through a qualitative methodology, at a descriptive level when perceiving and portraying the object; and exploratory in developing concepts related to the studied phenomenon. Of the techniques for data collection, it was decided to aim for greater depth by conducting discursive workshops, also incorporating other instruments such as a focus groups and the application of questionnaires in the actions of approaching participating readers to works available in the national digital libraries of Brazil and France. The study traced the mediation of reading in the digital environment, understanding that this is a process that involves diversity of elements and contexts, in addition to the use of technical instruments. In this way, we understand the relevance of considering subjective, social and cultural views in the construction of meanings attributed by the subjects when approaching objects and means.